Basic Techniques for Extremity Reconstruction External Fixator Applications According to Ilizarov Principles (Springer International Publishing, 2018)
This book provides detailed descriptions of fundamental techniques that may be employed for extremity reconstruction and distraction osteogenesis in accordance with the principles established by Gavriil Abramovich Ilizarov. Techniques of proven value for deformity correction, limb lengthening, reconstruction of post-traumatic and post-osteomyelitis bone defects, non-union surgery, and fracture fixation with external fixators are thoroughly described step by step with the aid of a wealth of illustrative material. In addition, indications and preoperative planning are clearly explained. Throughout, care is taken to highlight important technical tips and tricks as well as clinical pearls and pitfalls. Since the first description of distraction osteogenesis by Ilizarov in the 1950s, numerous technical improvements have been made and new devices, developed, even though the basic principles have remained the same. This new book will be of value for both novice and more experienced surgeons who use distraction osteogenesis for the purpose of extremity reconstruction.